Preparation of Proper Immunogen by Cloning and Stable Expression of cDNA coding for Human Hematopoietic Stem Cell Marker CD34 in NIH-3T3 Mouse Fibroblast Cell Line - Farzaneh Shafaghat; Hajar Abbasi-Kenarsari; Jafar Majidi; Ali Akbar Movassaghpour; Dariush Shanehbandi; Tohid Kazemi (Tabriz University of Medical Sciences, 2015)
Purpose: Transmembrane CD34 glycoprotein is the most important marker for identification, isolation and enumeration of hematopoietic stem cells (HSCs). We aimed in this study to clone the cDNA coding for human CD34 from KG1a cell line and stably express in mouse fibroblast cell line NIH-3T3. Such artificial cell line could be useful as proper immunogen for production of mouse monoclonal antibodies. Methods: CD34 cDNA was cloned from KG1a cell line after total RNA extraction and cDNA synthesis. Pfu DNA polymerase-amplified specific band was ligated to pGEMT-easy TA-cloning vector and sub-cloned in pCMV6-Neo expression vector. After transfection of NIH-3T3 cells using 3 μg of recombinant construct and 6 μl of JetPEI transfection reagent, stable expression was obtained by selection of cells by G418 antibiotic and confirmed by surface flow cytometry. Results: 1158 bp specific band was aligned completely to reference sequence in NCBI database corresponding to long isoform of human CD34. Transient and stable expression of human CD34 on transfected NIH-3T3 mouse fibroblast cells was achieved (25% and 95%, respectively) as shown by flow cytometry. Conclusion: Cloning and stable expression of human CD34 cDNA was successfully performed and validated by standard flow cytometric analysis. Due to murine origin of NIH-3T3 cell line, CD34-expressing NIH-3T3 cells could be useful as immunogen in production of diagnostic monoclonal antibodies against human CD34. This approach could bypass the need for purification of recombinant proteins produced in eukaryotic expression systems.